Demographic profile of Acute Pancreatitis in Eastern India: A Single Centre Experience - Mukherjee, Dibyendu; Bhakta, Shantanu; Lahiry, Sandeep; Sinha, Rajasree (Asian Journal of Medical Sciences, 2017)
Background: Little is known about the etiological risk factors of acute pancreatitis (AP) in Eastern India. Aims and Objective: The aim of this study is to assess current trends etiology of AP in Eastern India. Materials and Methods: A retrospective study with cross-sectional design was undertaken based on available medical records of patients admit between January 2014 and January 2017 with physician-assigned diagnoses of AP at KPC Medical College & Hospital, Kolkata (n = 234). Multivariate analyses were done to identify risk factors, and distribution was compared on the basis gender. Groups were selected on the basis of a working diagnosis. A stratified comparison was done in 3 commonest etiology groups identified: ‘alcohol’, ‘non-alcohol’ and ‘idiopathic’. Results: The commonest etiology was attributed to alcohol (29.4%), idiopathic cause (20.5%), and obstructive cause (14.5%). Prevalence of AP was higher with alcoholism in men (37% vs. 10.8%; p < 00.1), however, other causes like idiopathic cause (12.3% vs. 37.8%), duct obstruction (1.2% vs. 43.2%), obesity (6.1% vs. 24.3%), and hypertriglyceridemia (6.1% vs. 14.8%) were higher among females ( p < 0.001 for all comparisons). Compared to non-alcoholics, patients with idiopathic AP were more likely to be overweight ( p = 0.019) and have T2 DM ( p = 0.021). Moreover, impact assessment of T2 DM status further revealed that the risk of AP was even greater with obesity (Odds Ratio [OR] 1.37; 95% Confidence Interval [CI] 0.57 – 3.26; p = 0.047) and smoking (OR 1.72; 95% CI 1.0 – 2.97; p = 0.049). Eighteen cases (7.7%) of ‘severe’ AP were identified, mostly due to: trauma in 6 (2.5%), idiopathic in 6 (2.5%), gallstones in 4 (1.7%), and alcoholism in 2 (0.8%). Conclusion: Alcohol intake is the predominant etiological risk factor for acute pancreatitis in Eastern India. Gender and type 2 diabetes mellitus are important contributory determinants. Asian Journal of Medical Sciences Vol.8(6) 2017 24-29